Differential Development of Glucose Intolerance and Pancreatic Islet Adaptation in Multiple Diet Induced Obesity Models - Omar, Bilal (MDPI, 2012)
Background: The C57BL/6 mouse fed a high fat diet is a common and valuable model in experimental studies of obesity and type 2 diabetes (T2D). Different high fat diets are used and in order to determine which diet produces a model most accurately resembling human T2D, they need to be compared head-to-head. Methods: Four different diets, the 60% high fat diet (HFD) and the 58% high fat-high sucrose Surwit diet (HFHS) and their respective controls, were compared in C57BL/6J mice using glucose tolerance tests (IVGTT) and the euglycemic clamp. Results: Mice fed a HFD gained more weight than HFHS fed mice despite having similar energy intake. Both high fat diet models were glucose intolerant after eight weeks. Mice fed the HFD had elevated basal insulin, which was not seen in the HFHS group. The acute insulin response (AIR) was unchanged in the HFD group, but slightly increased in the HFHS diet group. The HFHS diet group had a threefold greater total insulin secretion during the IVGTT compared to its control, while no differences were seen in the HFD group. Insulin sensitivity was decreased fourfold in the HFD group, but not in the HFHS diet group. Conclusion: The HFD and HFHS diet models show differential effects on the development of insulin resistance and beta cell adaptation. These discrepancies are important to acknowledge in order to select the appropriate diet for specific studies.